Microanalysis at the atomic level - Pennycook, S; Jesson, D; McGibbon, M; McGibbon, A; Nellist, P; Browning, N (1995)
The optical arrangement of the high-resolution scanning transmission electron microscope (STEM) allows incoherent imaging conditions to be established simultaneously for both elastically and inelastically scattered electrons, with good detection efficiencies. For zone axis illumination and localized inelastic transitions, both images show a resolution governed by the incident probe intensity profile, with maximum intensity occuring when the probe is located over the atomic columns. The high intensity elastic signal may therefore be used as an atomic resolution reference image for the low intensity inelastic signal, allowing spectroscopy to be achieved from selected atomic columns or planes. The potential of this approach in a 300-kV STEM is discussed.